Efficient image updates using light fields - Choudhury B.; Pandey A.; Chandran S. (My University, 2025)
The light field rendering method is an interesting variation on achieving realism. Once authentic imagery has been acquired using a camera gantry, or a handheld camera, detailed novel views can be synthetically generated from various viewpoints. One common application of this technique is when a user "walks" through a virtual world. In this situation, only a subset of the previously stored light field is required, and considerable computation burden is encountered in processing the input light field to obtain this subset. In this paper, we show that appropriate portions of the light field can be cached at select "nodal points" that depend on the camera walk. Once spartanly and quickly cached, scenes can be rendered from any point on the walk efficiently. © 2006 Elsevier B.V. All rights reserved.